The Antiquities of Däbrä Zäyt Qǝddǝst Maryam (East Tǝgray, Ethiopia) - Nosnitsin, Denis (Aethiopica, 2011)
The article summarizes the results of the research at Däbrä Zäyt, one of the historical sites discovered by the team of the project Ethio-SPARE (Hamburg University, Hiob Ludolf Centre for Ethiopian Studies) in Gulo Mäḵäda, East Təgray. It presents different types of historical evidence (old church building of the site, an inscription, the church library) and focuses on the analysis of the fragments of the so-called “old Golden Gospel” of Däbrä Zäyt, written presumably by the same scribe as the one of the well-known ms. Vat. Aeth. 25.